The mediating role of social support in the evaluation of training effectiveness - Alvelos, R.; Ferreira, A. I.; Bates, R. (European Journal of Training and Development, 2015)
Purpose – The purpose of this study is to contribute to the understanding of factors that affect training effectiveness. According to the literature, social support, perceived content validity, transfer design, the motivation to improve work through learning and positive transfer, contribute to the effectiveness of training. Design/methodology/approach – The sample used consisted of 202 employees with ages between 18 and 60 years, working for an insurance company where they had training for a period of three months. Findings – The results show a relationship between perceived content validity and transfer design, as well as with the motivation to improve work through learning. A mediating role of social support was also evident in this relationship. Finally, the authors highlight the findings of the relationship between motivation to improve work through learning and positive transfer. Originality/value – These findings contribute to the literature by demonstrating how the role of social support can increase training effectiveness in organizations.